Efektivitas Penggunaan Teknologi Pendidikan dalam Meningkatkan Prestasi Belajar Siswa Sekolah Dasar - Hia, Alice Felicia Azaria; Wulandari, Tri; Rahmayani, Tria Rohana (Lembaga Yasin AlSys, 2025)
The integration of digital technology into primary school learning has become a central focus in contemporary education, responding to the rapid advancement of information technology. Technology functions not only as a supporting tool but also as a catalyst for pedagogical innovation, driving a shift from traditional teaching methods to more interactive and collaborative approaches. This study aims to examine the role of digital technology integration in enhancing the quality of primary education, particularly in terms of student motivation and academic achievement. Using a descriptive qualitative approach based on literature review, the article explores relevant studies on the integration of educational technology at the primary school level. The findings indicate that the use of multimedia resources, such as e-books, instructional videos, and online learning platforms—enriches students’ learning experiences and expands access to instructional content. Despite challenges such as limited infrastructure and inadequate teacher training, the implementation of digital technology has generally contributed positively to increasing student motivation and academic performance. Therefore, the integration of digital technology in primary education should be supported through teacher capacity building, infrastructure development, and adaptive and sustainable education policies.